The Patenting Dilemma in Mexican Public Universities: the Case of ICAT-UNAM - Roberto, Vega-González Luis (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Technologies and academic inventions are developed in the daily work of the faculties, centers and research institutes of public universities. Since not all of them have commercial potential we propose that they not necessarily must be subject to patenting, because they can be protected with other intellectual property figures. Although, in many cases the inventions have technical relevance and comply with the legal requirements, they do not have a market focus, therefore they are not susceptible to commercial exploitation, or even they are not oriented to the solution of a specific social problem. This work deals with the dilemma of which academic inventions must be subject to patent in a deep austerity environment. Patenting requires considerable time, financial and human resources and in a context that all type of resources in Mexican public universities are scarce and eventually are further reduced in times of deep austerity, special care must be taken with what is patented. Using the Case Study of an R&D public institute, in this article we develop a quick method for evaluating whether or not university academic inventions should be patented, using scientific, technological, commercial and financial relevance criteria once the invention complies with legal criteria.